Proconiini Sharpshooters of Argentina, with notes on its distribution, host plants, and natural enemies - Paradell, Susana Liria (2012)
The American tribe Proconiini (Hemiptera: Cicadellidae: Cicadellinae) is one of the largest groups of xylem-feeding insects and includes the majority of the known vectors of xylem-born phytopathogenic organisms. The significance of the pathogens that this group transmits gives them an important role as pests, mostly for citrus fruit, grapes, and almonds. Knowledge of these Hemiptera in Argentina is insufficient and fragmentary. Thus one of the aims of this paper is to summarize the available information of the Proconiini sharpshooters in Argentina. In addition, 14 species are mentioned for the first time in the country, and new distributional data are given for 18 species. Thirty-four new associations between sharpshooters and host plants are recorded. New records of egg parasitoids are given for Dechacona missionum, Molomea consolida, M. lineiceps, and Tapajosa similis.